Sarco-Osteoporosis: Prevalence and Association with Frailty in Chinese Community-Dwelling Older Adults - Yan-Jiao Wang; Yi Wang; Jun-Kun Zhan; Zhi-Yong Tang; Jie-Yu He; Pan Tan; Hui-Qian Deng; Wu Huang; You-Shuo Liu (International Journal of Endocrinology)
The aim was to apply AWGS criteria to estimate the prevalence of sarco-osteoporosis and investigate its relationship with frailty, in a sample of 316 community-dwelling Chinese older people. Regression analysis was performed using frailty as the dependent variable. The results showed that the prevalence rate of sarco-osteoporosis was 10.4% in older men and 15.1% in older women. ≧80 years old (OR 4.8; 95% CI, 3.05–10.76; P=0.027), women (OR 2.6; 95% CI, 1.18–2.76; P=0.036), and higher level of comorbidity (OR 3.71; 95% CI, 1.61–10.43; P=0.021) were independently associated with the likelihood of being sarco-osteoporosis. In the frail group, sarco-osteoporosis occurred in 26.3% of men, in 38.5% of women, and in lower proportion in the prefrail (13.6% of men; 16.2% of women) and nonfrail group (1.6% of men; 1.9% of women) (P<0.05, resp.). Furthermore, the likelihood of being frail/prefrail was substantially higher in the presence of sarco-osteoporosis (OR 4.16; 95% CI, 2.17–17.65; P=0.019 in men; and OR 4.67; 95% CI, 2.42–18.86; P=0.007 in women). The results indicate that patients with sarco-osteoporosis are more likely to be ≧80 yrs with higher burden of comorbidities and to have frailty/prefrailty, especially for women.